Strengthening the National Waqf Ecosystem through Legal Reform: An Analysis of Waqf Issues in the Provinces of Lampung and South Sumatra - Faisal, Faisal; Mu'in, Fathul; Edy, Relit Nur; Indra, Gandhi Liyorba; Santoso, Rudi Santoso (Institut Agama Islam Negeri Curup, 2024)
The study aims to identify waqf issues in Lampung and South Sumatra Provinces and explore potential solutions to develop a national waqf ecosystem that is more responsive to the development of time. This research employed empirical juridical research. The primary data was gathered through observations, interviews, and documentation with waqif (donors), nadzir (the administrators of Waqf), public figures, academics, and BWI (Indonesian Waqf Institution) of Lampung and South Sumatra. The secondary data were gathered from books, laws and regulations, judicial decisions, scientific journals, and websites. This study discovered that the challenges of Waqf in Lampung and South Sumatra Provinces comprised aspects of management and supervision, a lack of socialization and literacy, waqf fraud, and insufficient nadzir (donors) resources for creating profitable Waqf and waqf digitization. The solution is to enhance the national waqf ecosystem by reforming waqf laws to strengthen waqif, nadzir, and BWI. With the renewal of waqf law, a positive ecosystem will emerge, reducing waqf disputes and improving people's well-being.